Bone tools, ornaments and other unusual objects during the Middle to Upper Palaeolithic transition in Italy. (20th June 2020) - Arrighi, Simona; Moroni, Adriana; Tassoni, Laura; Boschin, Francesco; Badino, Federica; Bortolini, Eugenio; Boscato, Paolo; Crezzini, Jacopo; Figus, Carla; Forte, Manuela; Lugli, Federico; Marciani, Giulia; et al.
Abstract: The arrival of Modern Humans (MHs) in Europe between 50 ka and 39 ka coincides with significant changes in human behaviour, notably regarding the production of tools, the exploitation of resources and the systematic use of ornaments and colouring substances. The emergence of the so-called modern behaviour is usually associated with MHs, although claims of symbolic thinking in non-MH groups have been advanced in past decades. In this paper, we present a synthesis of the Italian evidence concerning bone tool manufacturing and the use of ornaments and pigments in the time span encompassing the replacement of Neandertals by MHs. Current data show that Mousterian bone tools were mostly obtained from bone fragments used "as is". Conversely an organized production of "finely shaped" bone tools is characteristic of the Uluzzian and the Protoaurignacian, and the complexity inherent in the manufacturing processes suggests that bone artefacts are not to be considered expedient. Some traces of symbolic activities are associated with Neandertals in northern Italy. Ornaments (mostly tusk shells) and pigments used for decorative purposes are well recorded during the Uluzzian. Their features and distribution suggest an intriguing cultural homogeneity within this technocomplex. The Protoaurignacian is characterized by a wider range of archaeological evidence, consisting of personal ornaments (mostly pierced gastropods), pigments and engraved items.